Distributed artificial intelligence meets machine learning learning in multi-agent environments ; ECAI '96 Workshop LDAIS, Budapest, Hungary, August 13, 1996 ; ICMAS '96 Workshop LIOME, Kyoto, Japan, December 10, 1996 ; selected papers - Weiss, Gerhard 1962- (Lecture notes in computer science, 1997)
This state-of-the-art report documents current and ongoing developments in the area of learning in DAI systems. It is indispensable reading for anybody active in the area and will serve as a valuable source of information and inspiration for AI and ML professionals wishing to learn about this new interdisciplinary field or to prepare themselves for doing relevant research.